The US-Mexico Border Human Development Index, 1990–2010. Issue 3 (3rd July 2017) - Anderson, Joan B.; Gerber, James
ABSTRACT: This paper updates the Border Human Development Index (BHDI), a quality of life index for comparing well-being in municipios [Mexican sub-state administrative units] and counties along the US-Mexico border from 1990 to 2010. The index, first published in 2004, is updated to include the 2010 census data. Empirical estimations show that the gap between the US and Mexican BHDI increased during the 2000–2010 decade. Many of the employment and income advantages of Mexican border communities have been lost due to a combination of internal and external pressures including US recessions, competition from China, US security measures that slow trade and other cross-border interactions, and drug-related violence that scares off tourists and shoppers from the US.